2017
DOI: 10.2196/mhealth.7199
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Acceptability of a Mobile Comprehensive HIV Prevention App for Men Who Have Sex With Men: A Pilot Study

Abstract: BackgroundMen who have sex with men (MSM) are the group most impacted by the human immunodeficiency virus (HIV) epidemic and the only subgroup in the United States among which new HIV diagnoses are not decreasing. To achieve the US National HIV/AIDS (acquired immunodeficiency syndrome) Strategy goals of reducing new diagnoses by 25%, high (eg, 30-50%) coverage of multiple HIV prevention interventions is needed in both urban and rural areas. Mobile phone “apps” are an important channel through which prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
145
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 31 publications
2
145
1
4
Order By: Relevance
“…Sullivan et al, conducted a pilot study to test the usability of a comprehensive, theory-based HIV prevention app for MSM [27**]. The HealthMindr app provides self-assessment tools, HIV prevention recommendations and reminders (e.g., condom use, HIV testing, PrEP screening), prevention and treatment service locators, and the ability to order free condoms and HIV test kits.…”
Section: Technology-based Interventions With Hst Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sullivan et al, conducted a pilot study to test the usability of a comprehensive, theory-based HIV prevention app for MSM [27**]. The HealthMindr app provides self-assessment tools, HIV prevention recommendations and reminders (e.g., condom use, HIV testing, PrEP screening), prevention and treatment service locators, and the ability to order free condoms and HIV test kits.…”
Section: Technology-based Interventions With Hst Distributionmentioning
confidence: 99%
“…Two additional US-based studies focus on increasing HIV testing among MSM. One study is adapting the HealthMindr app [27**] to deliver in-app messages that encourage MSM to engage in prevention services. The app will include a feature that allows users to order free HST kits [PI: Sullivan].…”
Section: Technology-based Interventions With Hst Distributionmentioning
confidence: 99%
“…However, despite the fact that there are over 800 medication adherence applications for a range of conditions, few have been widely studied [24]. Although some research is beginning to investigate use of daily text messaging to support PrEP adherence [25], a smartphone application targeting HIV prevention that includes PrEP screening [26], a smartphone application that incorporates PrEP adherence among MSM in an ongoing trial [27], to our knowledge there are no published studies on medication adherence smartphone applications for PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…More than 20% of all new HIV infections in the US are among young people aged [13][14][15][16][17][18][19][20][21][22][23][24], and 92% of these new infections are diagnosed in YMSMmaking them one of the largest risk groups for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Informed by extensive formative research, Dr. Patrick Sullivan of Emory University (one of iTech's Principal Investigators), with app developers from Keymind, developed and tested an HIV testing promotion app for adult MSM ("HealthMindr"). [21] Our initial formative research with YMSM [22] suggested interest in an HIV testing app like HealthMindr, but the youth agreed that it had to be adapted to be more culturally and developmentally appropriate for their peers.…”
Section: Introductionmentioning
confidence: 99%